1959
DOI: 10.1113/jphysiol.1959.sp006291
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral effects of nicotine and acetylcholine resembling those of sympathetic stimulation

Abstract: In this paper we extend observations which have been made on various peripheral effects of nicotine and acetylcholine, these being effects which resemble those of sympathetic stimulation. The pilomotor action of acetylcholine on the hairs of the cat's tail was described by von Briicke (1935); Coon & Rothman (1940) confirmed this and observed that nicotine had the same action. These workers began by studying the effect of acetylcholine in causing goose-flesh in the human forearm and then observed that small amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
1

Year Published

1961
1961
1985
1985

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(48 citation statements)
references
References 17 publications
2
45
1
Order By: Relevance
“…This nicotine-like substance causes a stimulation of autonomic ganglia which is short-lived and not followed by paralysis (Chen & Portman, 1954); consequently, the same effect can be produced repeatedly, and the compound appeared ideally suited to test the hypothesis (Burn et al, 1959) that the action of nicotine on the vessels of the rabbit ear, the cat nictitating membrane and piloerectors, and other organs supplied with sympathetic fibres was produced indirectly by a release of noradrenaline and not due to a direct action of the drug on the ganglia. The site of the stores from which the noradrenaline would be released could be either the sympathetic neurones or the tissue itself.…”
Section: Dimethylphenylpiperazinium Iodidementioning
confidence: 99%
“…This nicotine-like substance causes a stimulation of autonomic ganglia which is short-lived and not followed by paralysis (Chen & Portman, 1954); consequently, the same effect can be produced repeatedly, and the compound appeared ideally suited to test the hypothesis (Burn et al, 1959) that the action of nicotine on the vessels of the rabbit ear, the cat nictitating membrane and piloerectors, and other organs supplied with sympathetic fibres was produced indirectly by a release of noradrenaline and not due to a direct action of the drug on the ganglia. The site of the stores from which the noradrenaline would be released could be either the sympathetic neurones or the tissue itself.…”
Section: Dimethylphenylpiperazinium Iodidementioning
confidence: 99%
“…It can be considered that nicotine acts directly upon a-adrenoceptors as suggested by Burn, Leach, Rand & Thompson (1959) and Ferry (1963). The action of phenoxybenzamine on the flow rate can probably be explained as an inhibition of the direct action of nicotine, but the action of hexamethonium cannot be explained, and should be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that nicotine, in addition to its ganglion stimulating effect, can also have a direct action on smooth muscle, partly through an effect on the acetylcholine receptors and, to a lesser extent, on receptors sensitive to phenoxybenzamine (Day & Vane, 1963). In addition, it may liberate noradrenaline from peripheral stores (Burn, Leach, Rand & Thompson, 1959). Noradrenaline release by nicotine or an action of nicotine on phenoxybenzamine-Eensitive receptors did not seem to play a significant part in the present experiments as neither phenoxybenzamine nor tolazoline affected the response of the villi to nicotine.…”
Section: Discussionmentioning
confidence: 99%